Facilitating the Resettlement and Rights of Climate Refugees : an Argument for Developing Existing Principles and Practices. - Kent, Avidan (Routledge Studies in Environmental Migration, Displacement and Resettlement Ser., 2018)
One of the most significant impacts of climate change is migration. Yet, to date, climate-induced migrants are falling within what has been defined by some as a 'protection gap'. This book addresses this issue, first by identifying precisely where the gap exists, by reviewing the relevant legal tools that are available for those who are currently, and who will in the future be displaced because of climate change. The authors then address the relevant actors; the identity of those deserving protection (displaced individuals), as well as other bearers of rights (migration-hosting states) and obligations (polluting states) The authors also address head-on the contentious topic of definitions, concluding with the provocative assertion that the term 'climate refugees' is indeed correct and should be relied upon. The second part of the book looks to the future by advocating specific legal and institutional pathways. Notably, the authors support the use of international environmental law as the most adequate and suitable regime for the regulation of climate refugees. With respect to the role of institutions, the authors propose a model of 'cross-governance', through which a more inclusive and multi-faceted protection regime could be achieved. Addressing the regulation of climate refugees through a unique collaboration between a refugee lawyer and an environmental lawyer, this book will be of great interest to scholars and professionals in fields including international law, environmental studies, refugee studies and international relations.